Eliciting perspectives on remote healthcare delivery from service users with psychosis in the community: a cross-sectional survey study - Kuhn, Ronja; Abdel-Halim, Nadia; Healey, Patrick; Bird, Victoria; Elliot, Kathryn; McNamee, Philip (Frontiers in Digital Health, 2024)
Introduction: The transition towards remote healthcare has been rapidly accelerated in recent years due to a number of factors, including the COVID-19 pandemic, however, few studies have explored service users’ views of remote mental healthcare, particularly in community mental health settings. Methods: As part of a larger study concerned with the development of a remotely delivered psychosocial intervention, a survey was conducted with service users with psychosis (N=200) from six NHS trusts across England to gain cross-sectional data about service users’ opinions and attitudes towards remote interventions and explore how digital access varies across different demographic groups and geographical localities. Results: The majority of service users had access to technological devices and a quiet space to receive care. Age was a key factor in motivation to engage with remote care as older participants had less access to technological devices and the internet, and reported less confidence to learn how to use new technologies compared to younger participants. Differences in access and attitudes towards remote care were found across the different geographical localities. Over half of the participants (53.1%) preferred a hybrid model (i.e., mixture of face-to-face and remotely delivered treatment), with only 4.5% preferring remote treatment exclusively. Factors that both encourage and deter service users from engaging with remote care were identified. Conclusions: The findings of this study provide important information about the environmental and clinical barriers that prevent, or limit, the uptake of remotely delivered care for people with psychotic disorders. Although service users often have the ability and capacity to receive remote care, providers need to be cognisant of factors which may exacerbate digital exclusion and negatively impact the therapeutic alliance.